STEM-Based Biology Learning Assisted by Virtual Lab Gizmos to Enhance Critical Thinking Skills of Students with Different Academic Abilities - Jariah, Ainun; Bahri*, Arsad; Syamsiah, Syamsiah; HS, Syamsul Bahri (Universitas Syiah Kuala, 2025)
The critical thinking skills (CTS) of students with different academic abilities is still low. Therefore, STEM-based biology learning assisted by virtual lab gizmos can be implemented to improve students' CTS. This study aims to determine whether STEM-based biology learning assisted by virtual lab gizmos can enhance students' CTS with different academic abilities. This study employed a quasi-experimental design with a pretest-posttest control group design. The population consisted of twelfth-grade science students from SMA Negeri 3 Bantaeng. The sample was selected using simple random sampling, with a total of 60 students divided into two learning groups: XII MIPA 1 and XII MIPA 2. Data collection techniques included a CTS skills test. Data analysis was conducted using two-way analysis of covariance. The results showed STEM-based biology learning asissted by the virtual lab gizmos significantly enhances students' CTS, with a significance value of 0.00 0.05. Additionally, the study reveals that academic abilities also influences students' CTS. Furthermore, there is an interaction effect between STEM-based learning with the virtual lab gizmos and academic abilities on students' CTS. Further post hoc LSD analysis shows that STEM-based biology learning with the virtual lab gizmos is more effective in improving students' CTS across different academic abilities compared to contextual learning without the virtual lab gizmos. These findings suggest that STEM-based biology learning supported by the virtual lab gizmos can serve as an effective teaching strategy to enhance students' CTS, particularly in addressing the challenges of 21st-century education